Using Grinded Cane with Paraffin Wax in Interior Insulation of Buildings for Reducing Cooling Load - Hussein, Nassr (Journal of Engineering and Sustainable Development, 2024)
The present work aims to utilize a mixture of paraffin wax and grinded cane material as composite materials in building interior insulation. Two grinded cane material particle sizes (2 and 4 mm) were adopted. In addition, the effect of the mixing ratio of the grinded cane material (25, 50, and 75%) on enhancing mechanical, acoustic, and thermal performances was investigated.  Moreover, two building ceiling models commonly seen in Baghdad were used to calculate the cooling load reduction rate. The outcomes of the experiments showed that filling the work specimens with the composite material of large particle sizes of grinded cane contributed to reducing the thermal cooling load of buildings, where the reduction rate in cooling load for the first ceiling model reached 1.17% when mixing 75% of grinded cane large particles, while, for the second ceiling model, the reduction rate reached 1.02% for the same mixing ratio. Mechanical performance significantly improved in a range of 285 to 433%, 168 to 521%, and 57 to 81.5%, respectively, in both tensile, impact and flexural tests. Moreover, increasing the mixing ratio and the particle size of the grinded cane material offers superior mechanical properties and better acoustic performance, where the noise levels were reduced by a range of 4 to 7.5%.